The effect of the combination of thiotriazoline and corvitin on the values of some parameters of the cellular and humoral immune system during the experimental reproduction of allergic alveolitis under immobilization stress - Galii-Lutska, V. (Journal of Education, Health and Sport, 2022)
The purpose of the study was to determine the effectiveness of the combination of corvitin and thiotriazoline for the correction of levels of T- and B-lymphocytes, circulating immune complexes (CIC) of the blood of male guinea pigs (GP) if experimental allergic alveolitis (EAA) and immobilization stress (IS) are combined. The study was performed on 50 male GP weighing 180-210 g. EAA was reproduced by the method of O.O. Orekhov, Yu.A. Kyrylov. The production of IS was carried out by the method of P.D. Horizontov. The content of T- and B-lymphocytes in the blood was determined by the method of E.F. Chernushenko, L.S. Kogosova. CIC were detected by the method of Haskova V., Kaslik J., Math J., Matejckava M. The withdrawal from the experiment was carried out by the method of decapitation after previous administration of nalbuphine hydrochloride in the experimental group (EG) of intact GP; in the EG of EAA and IS during the study days corresponding to the stages of development of IS: 1st – anxiety, 14th – resistance, 24th – exhaustion; EG of EAA with IS on the 24th day after pharmacocorrection with the above-mentioned combination of drugs. There was a progressive decrease in the level of T-lymphocytes by 33,47% (p<0,01), 36,23% (p<0,01) and 39,62% (p<0,01), an increase in B-lymphocytes by 27,82% (p<0,01), 131,13% (p<0,01) and 44,37% (p<0,01), an increase in CIC by 41,15 % (p<0,01), 46,62% (p<0,01), and 50,78% (p<0,01) on the 1st, 14th and 24th days respectively, compared to the indicators of the control group under the combination of EAA and IS. An increase in T-lymphocytes by 40% (p<0,01), a decrease in B-lymphocytes by 24,31% (p<0,01), and a decrease in the level of CIC by 26,08% (p<0,01) were observed in the EG using corvitin and tiotriazoline relative to the corresponding indicators of the EG with a combination of EAA and IS without pharmacological interventions on 24th day of the experiment. The results indicate an immunocorrective effect of the combination of corvitin and thiotriazoline which is manifested by activation of the cellular and suppression of the humoral link of immunity of GP exposed to EAA and IS.